Midfielder as the prominent participant in the building attack: A network analysis of national teams in FIFA World Cup 2014 - Clemente, F. M.; Martins, F. M. L.; Wong, Del P.; Kalamaras, D.; Mendes, R. S. (International Journal of Performance Analysis in Sport, 2015)
This study aimed to analyze the most prominent players' positions that contributed to the build of attack in football during FIFA World Cup 2014. The connections among teammates in all matches of the tournament were analyzed, and the tactical lineup and players' positions of players were codified as independent variables. Four centrality network metrics were used to identify the pertinence of each players' position. A total of 37,864 passes between teammates were recorded. Each national team was analyzed in terms of all their matches, thus all 64 matches from the FIFA World Cup 2014 tournament were analyzed and codified in this study. A total of 128 adjacency matrices and corresponding network graphs were generated and used to compute the centrality metrics. Results revealed that the players' position (p = 0.001; ?2 p = 0.143; Power = 1.00; moderate effect size) showed significant main effects on centrality measures. The central midfielders possessed the main values in all centrality measures in the majority of analyzed tactical lineups. Therefore, this study showed that independent of the team strategy, the players' position of a central midfielder significantly contributed to the build of attack in football, for example, greater cooperation and activity profile.